PORTABLE ADSB MULTIPLE RECEIVER BASED ON RASPBERRY PI USING RTL-SDR - NYARIS PAMBUDIYATNO; BAMBANG BAGUS HARIANTO; YUYUN SUPRAPTO; ADE IRFANSYAH; ACHMAD SETIYO PRABOWO; RR.RETNO SAFITRI WULANDARI (Journal of Research in Social Science and Humanities, 2025)
Automatic Dependent Surveillance-Broadcast (ADS-B) is a technology used in aircraft monitoring systems, where aircraft transmit identity, position, speed, and other data via open radio signals. Receiving and decoding ADS-B signals to obtain real-time flight information have been of significant interest in the aviation field. In this study, we propose the implementation of a multi-receiver ADS-B system based on RTL-SDR (Software-Defined Radio) to enhance monitoring coverage and flight data accuracy. RTL-SDR is a cost-effective and versatile platform that uses hardware programmable through software to receive radio signals. To demonstrate the effectiveness and performance of the multi-receiver RTL-SDR-based ADS-B system, a series of experiments will be conducted in different environments, followed by a comparison of results with another platform, namely Flight Radar24. The system's performance will be evaluated, yielding a success rate of 83.8%, accuracy of 76.68%, and equipment sensitivity of 64.17 dBm. For Quality of Service (QoS) analysis, the obtained results are as follows: throughput falls under the category of very good, packet loss is categorized as moderate, delay is categorized as very good, and jitter is categorized as bad